Evaluation of the quality of banking service in the two branches of Al-Rafidain Bank / Al-Khadra and Al-Ma`rifa Bank: A comparative study - Naser Jebur, Luay (Iraqi Journal for Administrative Sciences, 2024)
This research aims to Know the extent to which some Rafidain Bank branches are committed to tangibles, reliability, responsiveness, assurance and empathy with customers when evaluating the perceived service quality, In light of the researcher’s field visit to the bank’s branches, it was found that the bank does not provide modern equipment such as automated teller machines (ATM), There is no response to the customers, and the customers remain for a long time until the demand is met, and this is the problem of the research, The importance of the research came to achieve the perceived service quality in suitability to the expectations or needs of customers to achieve customer satisfaction to maintain existing customers and earn more, The two branches of Al-Rafidain Bank / Al-Khadra and Al-Ma`rifah were selected, and the opinions of the customers of the two branches amounting to (90) samples were taken for research the questionnaire was used to measure the quality of service by equation analysis of the gap between the perceptions and expectations of customers, Rafidain Bank is one of the distinguished public sector banks, which must achieve customer satisfaction by applying the dimensions of service quality and achieving loyalty by ministries or organizations that have established the comprehensiveness of their employees with Rafidain Bank, and thus an increase in customers is achieved towards the investigated bank. The most important conclusions and recommendations there is a weakness in responding to customers and the lack of speed of performance to solve the problem of customers, so the recommendations appeared that it is necessary to put employees to meet the needs of customers when customers arrive at the bank and increase the flexibility and innovation of employees to meet the different needs and desires of customers and follow up customers and listen to their opinions in order to determine weakness In the perceived service quality and its treatment.